2019
DOI: 10.1111/cea.13460
|View full text |Cite
|
Sign up to set email alerts
|

FCER2 T2206C variant associated with FENO levels in asthmatic children using inhaled corticosteroids: The PACMAN study

Abstract: BackgroundThe FCER2 gene, via encoding of the CD23 receptor, plays an important role in the regulation of IgE responses. A genetic variant of the FCER2 gene (T2206C) was previously shown to be associated with IgE levels in asthmatic children. IgE sensitization has also been linked to increased levels of fractional exhaled nitric oxide (FENO).ObjectiveTo investigate whether the FCER2 T2206C variant influences FENO levels in asthmatic children with a reported use of inhaled corticosteroids (ICS).MethodsThis cros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 42 publications
0
13
0
Order By: Relevance
“…Between 2018 and 2019, the pharmacogenetic studies conducted in pediatric asthma have been mainly focused on therapeutic response to ICS and SABA albeit some of them have studied simultaneously the response to ICS and LABA/ LTRA. Altogether, eleven candidate-gene studies, [24][25][26][27][28][55][56][57][58][59] a meta-analysis of a candidate gene, 60 and six pharmacogenomic studies (one of them in adults but including replication in children) have been performed. 32,36,40,73,74,79 During this period, candidate-gene studies reported the association of genes previously described in pharmacogenetic studies of pediatric asthma with treatment response (ADRB2, GSDMB, FCER2, and VEGFA).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Between 2018 and 2019, the pharmacogenetic studies conducted in pediatric asthma have been mainly focused on therapeutic response to ICS and SABA albeit some of them have studied simultaneously the response to ICS and LABA/ LTRA. Altogether, eleven candidate-gene studies, [24][25][26][27][28][55][56][57][58][59] a meta-analysis of a candidate gene, 60 and six pharmacogenomic studies (one of them in adults but including replication in children) have been performed. 32,36,40,73,74,79 During this period, candidate-gene studies reported the association of genes previously described in pharmacogenetic studies of pediatric asthma with treatment response (ADRB2, GSDMB, FCER2, and VEGFA).…”
Section: Discussionmentioning
confidence: 99%
“…Several candidate-gene studies have been performed to evaluate the influence of genetic variants on treatment response to ICS (Table 2). 26,[54][55][56][57][58][59] Similarly to the response to SABA, the ADRB2 gene is one of the most extensively analyzed in pharmacogenetic studies of ICS. 16,18,23 In 2018, Sood et al 54 studied two SNPs (rs1042713 and rs1042714) from the ADRB2 gene in a European American and African American cohort (n=373) of children with asthma under ICS treatment.…”
Section: Candidate-gene Studies Of Ics Responsementioning
confidence: 99%
See 1 more Smart Citation
“…One area of intense current research interest in asthma is pharmacogenomics, that is evaluating genetic variants that might explain the response to treatment and lead to targeted asthma treatments based on genotype 2 . Karimi et al previously reported in this journal that a genetic variant in the low‐affinity IgE receptor may influence airway inflammation as measured by exhaled nitric oxide 3 . In this issue, the same group report work from the multiethnic Pharmacogenomics in Childhood Asthma (PiCA) consortium of 10 separate studies 4 .…”
Section: Figurementioning
confidence: 99%
“…In a study focused on polymorphism of a gene encoding the low affinity IgE receptor, CD23 (FCER2) was found to be associated with reduced FeNO levels in well controlled asthmatic children using ICS for asthma management. 61 The polymorphism in FCER2 was considered to lead to reduced expression of CD23 resulting in lower levels of IgE and reduced FeNO. However, the findings might be confounded by the direct effects of ICS on lowering FeNO, though in this study, ICS dosage was not correlated with FeNO.…”
Section: Biomarkers and Mechanisms Of Diseasementioning
confidence: 99%